2000
DOI: 10.1681/asn.v1191583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidosis on the Properties of the Glutaminase mRNA pH-Response Element Binding Protein

Abstract: Abstract. The pH-responsive stabilization of the rat renal glutaminase (GA) mRNA during metabolic acidosis is mediated by a pH-response element (pH-RE). The primary pH-RE within the GA mRNA consists of a direct repeat of an 8-base adenosine and uridine—rich sequence, which binds a specific cytosolic protein, the pH-response element binding protein (REBP). The functional analysis of this system was performed in LLC-PK1-F+ cells, a pH-responsive line of porcine proximal tubule-like cells. Cytosolic extracts of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 22 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…Thus, inhibition of GLS1 via 968 prevented cancer cells from being able to compensate for the acidification of their culturing media and caused them to become more sensitive to glutamine withdrawal. Moreover, Wagner and Curthoys independently showed that GLS1 expression is up-regulated in mice suffering from chronic acidosis, which is consistent with earlier findings showing that the mRNA encoding GLS1 contains a pH-responsive element that helps promote the stability of the transcript when exposed to acidic conditions. …”
Section: Introductionsupporting
confidence: 85%
“…Thus, inhibition of GLS1 via 968 prevented cancer cells from being able to compensate for the acidification of their culturing media and caused them to become more sensitive to glutamine withdrawal. Moreover, Wagner and Curthoys independently showed that GLS1 expression is up-regulated in mice suffering from chronic acidosis, which is consistent with earlier findings showing that the mRNA encoding GLS1 contains a pH-responsive element that helps promote the stability of the transcript when exposed to acidic conditions. …”
Section: Introductionsupporting
confidence: 85%